The excision theory for homology theory through A_∞-algebras - Karar, Faten Ragab; Mohammed, Fatma Elzhraa Ahmed; Fattah, A. A. El (Edelweiss Applied Science and Technology, 2024)
This paper investigated A_∞-algebras, which are generalizations of associative algebras that incorporate higher homotopy structures. We began by revisiting the fundamental definitions and properties of A_∞-algebras and their associated homological theories, providing a solid foundation for understanding these complex structures. The study included an in-depth analysis of simplicial homology as it relates to A_∞-algebras, focusing on significant results, particularly those concerning excision theory. In this context, we introduced new insights into the relationship between bar homology and simplicial homology, presenting a precise sequence elucidating the interaction between these two homological structures. Within this framework, we provided proofs for key results, such as the quantitative coherence of certain maps and the interchanging diagram that connects different homological categories. We address the specific failure of excision properties and its implications for long exact sequences in both homological and homotopical contexts. This paper offered a comprehensive overview of current developments in A_∞-algebra theory and simplicial cohomology, highlighting classical and contemporary insights into these sophisticated mathematical structures. By presenting detailed definitions, examples, and theorems, we strive to contribute to a deeper understanding of homology within the framework of advanced algebraic systems. Our analysis sheds light on existing theories and paves the way for future research in the field, providing a valuable resource for mathematicians interested in the interplay between algebra and topology.